Deep Learning in Islamic Religious Education Learning in the Disruption Era (A Study at SMA Negeri 1 Yosowilangun) - Munawaroh munaw et al, Siti; Jannah, Nur (Mu'allim, 2025)
The era of disruption has brought significant transformations in the education sector, including in the learning of Islamic Religious Education (PAI). The decline in students' interest and understanding of PAI materials is a major issue that requires deep attention. This requires educators to not only deliver information, but also to create meaningful, fun, and deep learning experiences. This study aims to explore the application of deep learning approach in PAI learning at SMA Negeri 1 Yosowilangun, emphasizing three main pillars: mindful learning, meaningful learning, and joyful learning. The research method used is qualitative with a phenomenological approach, and data collection techniques through observation, interviews, and documentation of teachers and students. The research findings show that the application of deep learning has a positive impact on improving the quality of students' understanding. The learning process is conducted with awareness, relevance to daily life, and fun through the application of methods such as Project Based Learning, Inquiry Discovery, and technology integration. In conclusion, the deep learning approach can help create a learning atmosphere that is reflective, innovative, and adaptive to the challenges of the disruption era, as well as being able to increase student motivation and engagement in PAI learning.